(untitled) - Hornback, Joseph M. (Belmont, 2006)
This is by far one of the best texts for undergraduate organic chemistry! The explanations are clear and concise, and ideas and concepts are well-organized. The book is easy to follow and the problems, both within and at the ends of the chapters, make the concepts crystal clear.
Keywords: Chemistry, organic